Dialectical Behavioral Therapy for Adolescents (DBT-A): a clinical Trial for Patients with suicidal and self-injurious Behavior and Borderline Symptoms with a one-year Follow-up - Schneider Csilla; Brück Christiane; Sixt Barbara; Böhme Renate; Fleischhaker Christian; Schulz Eberhard (BMC, 2011)
Abstract Background To date, there are no empirically validated treatments of good quality for adolescents showing suicidality and non-suicidal self-injurious behavior. Risk factors for suicide are impulsive and non-suicidal self-injurious behavior, depression, conduct disorders and child abuse. Behind this background, we tested the main hypothesis of our study; that Dialectical Behavioral Therapy for Adolescents is an effective treatment for these patients. Methods Dialectical Behavioral Therapy (DBT) has been developed by Marsha Linehan - especially for the outpatient treatment of chronically non-suicidal patients diagnosed with borderline personality disorder. The modified version of DBT for Adolescents (DBT-A) from Rathus & Miller has been adapted for a 16-24 week outpatient treatment in the German-speaking area by our group. The efficacy of treatment was measured by a pre-/post- comparison and a one-year follow-up with the aid of standardized instruments (SCL-90-R, CBCL, YSR, ILC, CGI). Results In the pilot study, 12 adolescents were treated. At the beginning of therapy, 83% of patients fulfilled five or more DSM-IV criteria for borderline personality disorder. From the beginning of therapy to one year after its end, the mean value of these diagnostic criteria decreased significantly from 5.8 to 2.75. 75% of patients were kept in therapy. For the behavioral domains according to the SCL-90-R and YSR, we have found effect sizes between 0.54 and 2.14. During treatment, non-suicidal self-injurious behavior reduced significantly. Before the start of therapy, 8 of 12 patients had attempted suicide at least once. There were neither suicidal attempts during treatment with DBT-A nor at the one-year follow-up. Conclusions The promising results suggest that the interventions were well accepted by the patients and their families, and were associated with improvement in multiple domains including suicidality, non-suicidal self-injurious behavior, emotion dysregulation and depression from the beginning of therapy to the one-year follow-up.